腫瘍環境改変によるマクロファージ活性化機構の解明 - 山口, 雄大; 西出, 峻治; 三浦, 克之; 冨田, 修平; 松永, 慎司; 塩田, 正之 (日本薬理学会年会要旨集, 2019)
Tumor tissue environment is generally exposed to low oxygen, nutrition depletion and high interstitial pressure condition. These circumstances are caused by vascular hyper-permeability, irregular vascularization and immature vessels. We previously reported that prolyl hydroxylase inhibitor (PHDi) induced tumor blood vessel normalization and improved tumor microenvironment (TME) in tumor bearing mouse. In this study, we examined whether improvement of TME by PHDi elicit phenotypic alteration of tumor infiltrated immune cells, especially macrophage (Mf). Lewis lung carcinoma cells were transplanted subcutaneously. Mice were treated with PHDi intraperitoneally at day10 after tumor transplantation. Then tumor tissues were collected at day16 and analyzed immune cells by flowcytometry and immunofluorescence staining. we performed phagocytosis assay using sorted Mf from tumor tissue and bone derived Mf. Mf ratio in total leukocyte were significantly increased in PHDi treated tumor in both immunohistochemical and flowcytometric analysis. Lymphocyte ratio didn't change in PHDi treated tumor. Both in vivo and ex vivo experiments showed that phagocytosis ability of Mf increased about 1.5 folds in PHDi treated Mf. these Mfs may affect tumor progression.